The Role of Inhibition in Age-related Off-Topic Verbosity: Not Access but Deletion and Restraint Functions - Yin, Shufei; Peng, Huamao (Frontiers in Psychology, 2016)
The speech of older adults is commonly described as verbose and off-topic, which is thought to influence their social communication. This study investigated the role of inhibition in age-related off-topic verbosity (OTV). Inhibition consists of three functions: access, deletion, and restraint. The access function is responsible for preventing irrelevant information from accessing the attention center (pre-mechanism of inhibition); The deletion function is responsible for deleting previously relevant but currently irrelevant information from working memory, and the restraint function is responsible for restraining strong but inappropriate responses (post-mechanisms of inhibition). A referential communication task was used to determine whether OTV was influenced by the pre-mechanism of inhibition. A self-involved event interview task was used to investigate the effect of the post-mechanisms of inhibition on OTV. Results showed that the OTV of the elderly participants was associated with an age-related decline in the post-mechanisms of inhibition, while the OTV exhibited by young adults was most likely due to deficits in the pre-mechanism function of inhibition. This research contributed to fill gaps in the existing knowledge about the potential relationship between specific functions of inhibition and age-related OTV.